Montmorency cherry supplementation improves 15-km cycling time-trial performance - Morgan, P. T.; Barton, M. J.; Bowtell, J. L. (European Journal of Applied Physiology, 2019)
Aim: Montmorency cherries are rich in polyphenols that possess antioxidant, anti-inflammatory and vasoactive properties. We investigated whether 7-day Montmorency cherry powder supplementation improved cycling time-trial (TT) performance. Methods: 8 trained male cyclists (VO2peak: 62.3 ± 10.1 ml/kg/min) completed 10-min steady-state (SS) cycling at ~ 65% VO2peak followed by a 15-km TT on two occasions. Participants consumed 6 pills per day (Montmorency cherry powder, MC; anthocyanin 257 mg/day or dextrose powder, PL) for a 7-day period, 3 pills in the morning and evening. Capillary blood [lactate] was measured at baseline, post SS and post TT. Pulmonary gas exchange and tissue oxygenation index (TOI) of m. vastus lateralis via near-infrared spectroscopy, were measured throughout. Results: TT completion time was 4.6 ± 2.9% faster following MC (1506 ± 86 s) supplementation compared to PL (1580 ± 102 s; P = 0.004). Blood [lactate] was significantly higher in MC after SS (PL: 4.4 ± 2.1 vs. MC: 6.7 ± 3.3 mM, P = 0.017) alongside an elevated baseline TOI (PL: 68.7 ± 2.1 vs. MC: 70.4 ± 2.3%, P = 0.018). Discussion: Montmorency cherry supplementation improved 15-km cycling TT performance. This improvement in exercise performance was accompanied by enhanced muscle oxygenation suggesting that the vasoactive properties of the Montmorency cherry polyphenols may underpin the ergogenic effects.